Antibiotics sensitivity and resistant pattern in tribal region of Chhattisgarh, India: a retrospective observational study - Bharti, Rupendra K.; Sharma, Raj K.; Sharma, Sanat K.; Mourya, Suresh K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Antimicrobial resistance (AMR) is the biggest health care problem globally, it is responsible for the high rate of mortality worldwide which was commonly observed in developing countries. We tried to find the incidence of antimicrobial resistance in the tribal region of Chhattisgarh, India. Methods: It was an institutional based retrospective observational study. Out of 3389 samples from inpatient and outpatient department, a total number of 1676 cultured proven micro-organism were isolated from Jan 2017 to Dec 2018. SPSS v23 was used for descriptive analysis. Results: More than 75% of the samples collected from the inpatient department in which surgical IPD were significantly higher. The commonest isolated were Staphylococcus aureus followed by Escherichia coli, then Klebsiella species. Amoxycillin-clavulanic acid was resistant to the majority of microorganism followed by 3rd generation cephalosporins then Co-trimoxazole. Conclusions: Antimicrobial resistance was higher even in the tribal region. The incidence of AMR is increasing at an alarming rate. Microorganism targeted antimicrobial therapy with the use of narrow-spectrum antibiotics and avoidance of broad-spectrum antibiotics will possibly overcome the antimicrobial resistance. There is also a need to strengthen laboratory or microbiology department to produce an accurate report to combat antimicrobial resistance.